Semiotic analysis of Islamic moral messages in soap operas "Buku Harian Seorang Istri" on SCTV - Qudratullah Qudratullah; Nurmalia Nurmalia; Ayu Wulandari (Islamic Communication Journal, 2023)
Television is not only a means of information but also influences the audience based on views, attitudes and norms. This study discusses the Islamic moral messages in the soap opera "Buku Harian Seorang Istri (Diary of a Wife)" on SCTV to find out the meaning of denotations, connotations, myths and provide an understanding of the moral messages contained in the soap opera. This study uses a type of qualitative research, with a library approach and Roland Barthes semiotic analysis. Furthermore, the data sources used are primary and secondary data with documentation data collection techniques. The results of this study indicate that the meaning of denotation in the soap opera "Buku Harian Seorang Istri" provides an overview of the dynamics of household life. The connotative meaning of the soap opera scene conveys the meaning that household life is a responsibility that must be carried out by both parties which must complement each other. The meaning of myth in this soap opera contains messages related to morality. This morality is related to human relations with other humans in the social sphere. This study contributes to strengthening moral values in media works (soap operas) as the basis for the development of a moral society.Â ***Televisi tidak hanya sebagai sarana informasi tetapi juga mempengaruhi khalayak berdasarkan pandangan, sikap, dan norma. Penelitian ini membahas pesan moral dalam sinetron â€œBuku Harian Seorang Istriâ€ di SCTV untuk mengetahui makna denotasi, konotasi, mitos dan memberikan pemahaman pesan moral yang terdapat dalam sinetron tersebut. Penelitian ini menggunakan jenis penelitian kualitatif, dengan pendekatan kepustakaan dan analisis semiotika Roland Barthes. Selanjutnya sumber data yang digunakan adalah data primer dan sekunder dengan teknik pengumpulan data dokumentasi. Hasil penelitian ini menunjukkan bahwa makna denotasi dalam sinetron â€œBuku Harian Seorang Istriâ€ memberikan gambaran tentang dinamika kehidupan rumah tangga. Makna konotatif dari adegan sinetron tersebut memberikan makna bahwa kehidupan rumah tangga merupakan tanggung jawab yang harus dilakukan oleh kedua belah pihak yang harus saling melengkapi. Makna mitos dalam sinetron ini mengandung pesan yang berkaitan dengan moralitas. Moralitas ini berkaitan dengan hubungan manusia dengan manusia lainnya dalam lingkup sosial. Studi ini berkontribusi bagi penguatan nilai moral dalam karya media (sinetron) sebagai basis pengembangan masyarakat yang bermoral.